P056 Transcriptional profiling of intestinal epithelial organoids derived from paediatric Crohn's disease patients. (25th January 2019) - Dotti, I; Ferrer-Picón, E; Planell, N; Martín de Carpi, J; Pujol, G; Masamunt, M; Esteller, M; Carrasco, A; Alvarez, L; Tristán, E; Ordás, I; Esteve, M; et al.
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory bowel disease (IBD) with onset occurring from childhood to late age. Despite a comparable genetic susceptibility, disease phenotype and natural history vary between paediatric and adult-onset CD. Recent studies have highlighted the importance of the intestinal epithelial barrier in the pathogenesis of IBD [1] [2] [3]. We hypothesise that the intestinal epithelium of patients with CD is characterised by age-dependent differences in the gene expression signature. Methods: Biopsy samples from the ileum and colon of paediatric and adult patients with CD were collected. Isolated crypt units were used to generate epithelial organoid cultures (EpOCs). After ex vivo expansion, EpOCs were induced to differentiate into the main lineages (d-EpOCs), and total RNA was extracted for expression profiling by microarray. Results: Paediatric and adult EpOCs followed similar differentiation programmes when induced to generate d-EpOCs, while maintaining a colon vs. ileum-specific pattern of marker expression. Nonetheless, a panel of genes was significantly altered in colonic EpOCs generated from paediatric vs. adult CD patients. Several of these genes were associated with the induction of a pro-inflammatory response (ie, CXCL gene family, REG1A, RETNLB). Conclusions: Our results suggest that paediatric patients with CD harbour specific lasting alterations in the epithelial compartment. This could contribute to differently shaping the phenotype of the disease in these patients. References 1. Planell N, Lozano JJ, Mora-Buch R, et al. Transcriptional analysis of the intestinal mucosa of patients with ulcerative colitis in remission reveals lasting epithelial cell alterations. Gut 2013;62:967–76. 2. Mora-Buch R, Dotti I, Planell N, et al . Epithelial IL-1R2 acts as a homeostatic regulator during remission of ulcerative colitis. Mucosal Immunol . 2016;9:950–9. 3. Dotti I, Mora-Buch R1, Ferrer-Picón E, et al. Alterations in the epithelial stem cell compartment could contribute to permanent changes in the mucosa of patients with ulcerative colitis. Gut. 2017;66:2069–79.